Influence of shipping activities on air pollutant concentrations in Klang and Penang, Malaysia - Jassim, Omar Ali (2013)
Air pollution is the presence of substances in air, so as to be, or bluster to be a threat to humanity, plant or animal life, or to property. Air pollutants emerge from both man made and natural processes. Pollutants are also defined as primary pollutants resulting from combustion of fuels and industrial operations and secondary pollutants,those which are produced because the reaction of primary pollutants in the atmosphere. Ship emissions are remarkable growing globally and have significantly influenced on air quality on sea and land. These emissions engage dangerous adverse health and environmental effects. Territorial waters, inland seas and ports are the regions most affected by vessel emissions. The aim of this work is to investigate air pollution levels due to shipping activities along the Strait of Malacca. This study was conducted to assess the level of air pollution and to investigate the level of air pollution from emission gases due to shipping activities in the Strait of Malacca. Six air quality stations which were close to the coast area were selected from Department of Environment (DOE) database for collecting data during 2000 to 2010. Furthermore the related data to ship traffic (type and numbers) were collected in the same period from the Malaysian Marine Department. Meteorological parameters and wind direction were also obtained from the Meteorological Department of Malaysia. Descriptive statistics, spatial distribution, Principle Component Analysis and regression analysis are employed to achieve the objectives. Data of vessels passing this strait indicates that the strait indeed has a high volume of patronage and this is likely to increase as the years roll. The analysis of the concentration of five air pollutants (NO2, CO, SO2, O3 and PM10) shows that their concentrations have an increasing trend from 2000 to 2010. The results of the spatial distribution also revealed that these air pollutants are concentrated towards the middle region of the Strait of Malacca. Principle Component Analysis categorized all air pollutants in two groups. CO, NO2 and SO2 were the most important pollutants across the Strait of Malacca. The result of regression analysis indicated a positive and significant positive relationship of number of vessels on the concentrations of CO, SO2, and NO2 while it was not significant for PM10 and O3 concentrations.